2015
DOI: 10.1017/s1368980015000890
|View full text |Cite
|
Sign up to set email alerts
|

Secular changes in intakes of foods among New Zealand adults from 1997 to 2008/09

Abstract: Objective: To examine changes in the food choices of New Zealand (NZ) adults, between the 1997 National Nutrition Survey (NNS97) and the 2008/09 NZ Adult Nutrition Survey (2008/09 NZANS). Design: The 2008/09 NZANS and the NNS97 were cross-sectional surveys of NZ adults (aged 15 years and over). Dietary intake data were collected using a computer-based 24 h diet recall. Logistic regression models were used to examine changes over time in the percentage reporting each food group, with survey year, sex and age gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…A likely explanation for the low improvement in global compliance is that the increase in compliance with some guidelines (i.e., fruits and vegetables) was compensated by the decrease in compliance with other guidelines (i.e., dairy) [27]. Compliance with fruits and vegetables guidelines increased in all studied groups, a finding also found in France [28] and in the United States [11], but not in New Zealand [10]. The increase in compliance with the vegetable guideline is likely due to the increased availability of vegetables in Switzerland between 1961 and 2007 [29].…”
Section: Trends In Compliance With Dietary Guidelinesmentioning
confidence: 85%
See 1 more Smart Citation
“…A likely explanation for the low improvement in global compliance is that the increase in compliance with some guidelines (i.e., fruits and vegetables) was compensated by the decrease in compliance with other guidelines (i.e., dairy) [27]. Compliance with fruits and vegetables guidelines increased in all studied groups, a finding also found in France [28] and in the United States [11], but not in New Zealand [10]. The increase in compliance with the vegetable guideline is likely due to the increased availability of vegetables in Switzerland between 1961 and 2007 [29].…”
Section: Trends In Compliance With Dietary Guidelinesmentioning
confidence: 85%
“…Compliance with dietary recommendations is an important factor for health maintenance and disease prevention [6], but several studies have shown that compliance with national dietary guidelines is low [7,8]. Still, of the few studies that assessed trends in compliance with dietary guidelines [9][10][11][12], some focused on a single guideline [11] or on a specific group of the population [12]. In Switzerland, the dietary guidelines were first issued by the Swiss society of nutrition in 1998, and again in 2011 [5,13].…”
Section: Introductionmentioning
confidence: 99%
“…Although FFQs have previously been developed and validated to evaluate multi‐nutrient intake in New Zealand adults, four out of five were developed over 15 years ago. These are no longer suitable due to changes in the dietary intake of New Zealanders . The most recent FFQ developed for New Zealand adults included 154 food items and was validated against an 8‐day food record and biomarkers in adult males and females primarily of European ethnicity .…”
Section: Introductionmentioning
confidence: 99%
“…These are no longer suitable due to changes in the dietary intake of New Zealanders. 11 The most recent FFQ developed for New Zealand adults included 154 food items and was validated against an 8-day food record and biomarkers in adult males and females primarily of European ethnicity. 5 It demonstrated good validity for ranking individual's nutrient intake, however, it's applicability for use in other ethnic groups may be limited.…”
Section: Introductionmentioning
confidence: 99%
“…Asian Indian immigrants living in United States have also shown lower intake of vegetables and more intake of dairy than the recommended amounts; though there were variations within the Asian Indian group regarding the intake of dietary items [40]. An earlier study has shown that Southeast Asian immigrants have a higher intake of red meat as compared to South Asian immigrants living in New Zealand [41]. The generalizability of our results might not be possible to South Asian and Javanese Surinamese populations living as immigrants in other western countries due to different food environments but these comparisons between Asian groups living in different western countries may be illustrative of the consistency of traditional dietary habits, despite differing migration trajectories.…”
Section: Discussionmentioning
confidence: 99%